Un ejemplo de reelaboración de un cuento de animales en dos novelas picarescas (Alonso, mozo de muchos amos y Lazarillo de Manzanares) - Arciello, Daniele (2020)
The key characteristic of Seventeenth century literature was the binding connection between oral tradition and written production. The two elements gave birth to what is currently considered as one of the most significant cultural prosperity age for Spain. Taking into account these considerations, the present article proposes to analyse the re-elaboration of a folkloric animal tale in two works attributed to the picaresque genre. After a review of the central aspects of protagonists’ personality in the novels in question, it will be highlighted each author’s personal contributions, as a result of the remodelling of the tale, subjugated to their ethic-literary intentions.
Característica clave de la literatura áurea fue el indisoluble vínculo entre tradición oral y producción escrita; estos dos elementos dieron lugar a aquello que hoy consideramos como una de las épocas de mayor florecimiento cultural de la península. Teniendo en cuenta dichas consideraciones, el presente artículo propone observar cómo un cuento folklórico de animales se reelabora en dos obras adscritas al género picaresco. Tras un repaso de los aspectos medulares de los protagonistas de las novelas en cuestión, se pondrán de relieve las aportaciones personales de cada uno de los autores analizados a la hora de moldear el cuento, subyugándolo a sus pretensiones ético-literarias.
Keywords: Cuentos; Crítica literaria; Novela picaresca